Pengaruh Religiusitas, Dukungan Sosial dan Demografi Terhadap Posttraumatic Growth Pada Remaja Pasca Perceraian Orang Tua - Rosita Djuhudi (Jurnal Ilmiah Multidisiplin Amsir, 2023)
This study was conducted to determine the religiosity effect, social support and demographics towards adolescent of victims’ divorce. The researches assume that religiosity (intellect, ideology, public practice, private practice, and religious experience), social support (informational support, emotional support, companionship support, and tangible support), gender, and age influence posttraumatic growth toward adolescent victims of parental divorce. The population of this research is teenagers of parents’ divorce victims who numbered 125 adolescents aged 12-18 years in West Sulawesi. Researchers use the accidental sampling technique which is one technique of non-probability sampling. Test the validity of measuring instruments using the technique of Confirmatory Factor Analysis (CFA). Data analysis using multiple regression analysis technique. The result of the research shows that there is a significant effect of the social support dimension on the posttraumatic growth variable of adolescent parent victims of divorce. The result of the study found that there was a significant influence of religiosity, social support, and demographic variables on posttraumatic growth towards adolescents of victim divorce. Significant variables were emotional support and tangible support and variables not significant were intellect, ideology, public practice, private practice, religious experience, informational support, companionship support, gender, and age. The researchers hope the implications of this study can be reviewed and improved in further research. It is exampled by adding other variables such as personal factors, cultural factors, and further broaden of respondents’ scope.